2001
DOI: 10.1007/s004420100645
|View full text |Cite
|
Sign up to set email alerts
|

Relative growth rate in phylogenetically related deciduous and evergreen woody species

Abstract: Relative growth rate (RGR) and other growth parameters were studied in eight pairs of closely related deciduous and evergreen species (within the same genus or family). The main objective of this study was to test the association between leaf turnover rate and RGR, specific leaf area (SLA, leaf area/leaf dry weight) and other growth variables. Plants were grown for 6 months in a greenhouse under favourable water and nutrient conditions. Variation in RGR among the 16 woody species was due mainly to differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
114
6
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 33 publications
13
114
6
18
Order By: Relevance
“…In our study, provenances showed no statistically significant variation in the RGR. The variation in RGR in woody species is generally assumed to be related to the variation in leaf area ratio (LAR) and to be greater in deciduous species compared to evergreens (Antunez et al, 2001). Physiological mechanisms (Walter et In the present study, there were significant differences among provenances in seed germination percentage, varying from 26.6% to 91.2% (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…In our study, provenances showed no statistically significant variation in the RGR. The variation in RGR in woody species is generally assumed to be related to the variation in leaf area ratio (LAR) and to be greater in deciduous species compared to evergreens (Antunez et al, 2001). Physiological mechanisms (Walter et In the present study, there were significant differences among provenances in seed germination percentage, varying from 26.6% to 91.2% (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Desta maneira, existe correlação entre crescimento e taxa de expansão da AF e as espécies com alta AFE e alta TCR, aparentemente produzem folhas com baixo investimento em biomassa. Portanto, segundo Antúnez et al (2001), as diferenças na AFE entre espécies se associam ao espessamento foliar determinado pelo genótipo. Wang et al (1994) indicam que as alterações nos parâmetros relacionados à morfologia foliar, como RAF, RMF e AFE, observados com o aumento da idade das plantas, revelam a capacidade de adaptação das folhas às condições variáveis da radiação ao longo do crescimento e desenvolvimento da planta.…”
Section: Resultsunclassified
“…Por tal motivo, o incremento da AF é uma medida estratégica para maximizar a superfície da folha, refletindo a área disponível para a absorção de luz por unidade de fotoassimilado investido (Marañon & Grubb 1993). Dessa forma, e concordando com Antúnez et al (2001), a maior TCR de M. peruiferum, pode ser explicada pelo incremento da AF, evidenciado pelas variações na RAF (figura 1B) e na AFE (figura 1C) entre 7 e 10 meses de idade, já que esta espécie não apresentou incremento na RMF nesse mesmo período, embora a RMF tenha sido alta nas duas idades (figura 1D). Segundo Grotkopp & Rejmánek (2007), uma alta AFE permite maior eficiência na captura da energia solar e é a partir da fotossíntese, em condições nutricionais ótimas, que a capacidade competitiva se evidencia.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The best equations to fit the relations were chosen by regression procedures with selection of forward, backward and stepwise methods. The relationship between the infection percentages by FOS and MPH and three groups of branch number and seed colour were analysed comparing the slopes of the linear regressions using a covariance analysis (Antunez et al 2001). The purpose of this statistical analysis was to determine the variables that significantly contribute to the variation of resistance to the Fusarium wilt and charcoal rot diseases in the sesame accessions.…”
Section: Methodsmentioning
confidence: 99%